Lost in memories: interacting with photo collections on PDAs - Harada, Susumu; Naaman, Mor; Song, Yee Jiun; Wang, QianYing; Paepcke, Andreas (Proceedings of the 4th ACM/IEEE-CS Joint Conference on Digital Libraries, 2004)
We developed two browsers to support large personal photo collections on PDAs. Our first browser is based on a traditional, folder-based layout that utilizes either the user's manually created organization structure, or a system-generated structure. Our second browser uses a novel interface that is based on a vertical, zoomable timeline. This timeline browser does not require users to organize their photos, but instead, relies solely on system-generated structure. Our system creates a hierarchical structure of the user's photos by applying time-based clustering to identify subsets of photos that are likely to be related. In a user experiment, we compared users' searching and browsing performance across these browsers, using each user's own photo collection. Photo collection sizes varied between 500 and 3000 photographs Our results show that our timeline browser is at least as effective for searching and browsing tasks as a traditional browser that requires users to manually organize their photos.